Readiness to Adopt New Technology: The Role of Psychological Capital and Technology Readiness - Anissa Lestari Kadiyono; Andrea Pardosi (Jurnal Penelitian Pendidikan IPA, 2023)
The industrial revolution has been the main driver in accelerating the use of technology. The use of technology in automation or data analytics has fundamentally changed the way of working, including at school. The research objective is to highlight the readiness of individuals to adopt new technologies, exploring the important role of psychological capital and technology readiness in this context. The main focus is on the influence of psychological capital, as well as technological readiness, on the likelihood of an individual adopting new technologies. The theories used as the basis of the research are psychological capital and technology readiness. The research was conducted on 403 teacher respondents in Indonesia using a nonprobability sampling method, namely quota sampling. Respondents were obtained by distributing online questionnaires. This research is non-experimental correlational research that is processed quantitatively. The measuring instrument used the Psychological Capital Questionnaire which has been adapted into 4 dimensions and 12 items and the Technology Readiness Index 2.0 which was adapted into 4 dimensions and 8 items. There is a positive correlational relationship between the two variables. An increase in psychological capital increases teachers' technology readiness scores, meaning teachers' positive psychological state can increase their propensity to adopt technology